Pharmacovigilance study of angiotensin-converting enzyme inhibitors in patients visiting Department of Medicine of a Tertiary Care Hospital, Surendranagar, Gujarat - Trivedi, Madhav D.; Kotadiya, Fenilkumar S.; Bavaliya, Manish K.; Tilva, Bhautik V.; Mehta, Dimple S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of this study was to evaluate incidence, patterns, and severity of angiotensin-converting enzyme inhibitor (ACEI) induced adverse drug reactions (ADR). Methods: A total of 500 hypertensive patients taking ACEI was enrolled in the study by taking an informed consent. Reporting of all ACEI-induced ADRs was done by filling CDSCO ADR form. All ADR reports were evaluated according to WHO-UMC causality assessment scale. Results: A total of 53 ADRs (31 males and 22 females) was observed in 500 hypertensive patients taking ACEI. Of 53 ADRs, 22 (41.51%) were mild, 28 (52.83%) were moderate, and only 3 (5.66%) were classified as severe. 7 ADRs (13.21%) were classified as certain, 30 ADRs (56.60%) were in probable category, 8 (15.09%) were in possible category, 4 (7.55%) in unlikely category, 3 (5.66%) in conditional category (unclassified), and 1 ADR was in unassessable (unclassifiable) category. Among 53 ADRs, 24 (4.80%) patients developed dry cough, 8 (1.60%) hypotension, 2 (0.40%) headache, 2 (0.40%) dizziness, 3 (0.60%) nausea/bowel upset, 3 (0.60%) rashes, 2 (0.40%) developed angioedema, 3 (0.60%) dysgeusia, hyperkalemia, acute renal failure, proteinuria are rare. Conclusions: Incidence of ADRs by ACEIs is 10.60% with cough as the most common ADR followed by hypotension. As enalapril is most frequently used ACEI, ADRs due to enalapril are more common.